Reagentless biosensor for isocitrate using one step modified Pt-Ir microelectrode - Pereira, A. C.; Fertonani, F. L.; Neto, G. D.; Kubota, L. T.; Yamanaka, H. (Elsevier B.V., 2001)
The Pt-Ir microelectrode modified through one step, electropolymerization is proposed for the isocitrate amperometric biosensor construction. The enzyme (isocitrate dehydrogenase-ICDH), coenzyme (NADP(+)) and mediator (Meldola's Blue) were immobilized onto the microelectrode surface in one step from a PIPES buffer solution containing pyrrole. The optimized experimental conditions were 25 cycles of cyclic voltammetric in a solution containing 3.58 10(-5) mol l(-1) of mediator, 3.51 10(-4) mol l(-1) of coenzyme and 2.68 U ml(-1) of enzyme. In contrast to the biosensor for isocitrate reported in literature, just one enzyme was immobilized and no coenzyme addition in the solution of analysis was necessary. Catalytic currents were proportional to the isocitrate concentration between 7.7 10(-6) and 1.04 10(-4) mol l(-1), showing good repeatability. The detection limit of the proposed biosensor was 3.50 10(-6) mol l(-1), the response time was lower than 20 s, the lifetime was about 30 determinations and no significant interference of sugars and citric acid was verified. Orange juice samples were analysed by both methodology biosensor and spectrophotometric commercial kit, and the obtained results presented a good correlation. The data demonstrated that the developed biosensor is suitable for isocitrate determination in orange juice without matrix interferences. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: isocitrate; biosensor; Pt-Ir microelectrode